Kafka's last love - Diamant, Kathi (Basic Books, 2003)
Profiles the life of Dora Diamant, the last love of Franz Kafka, describing the last year of his life they spent together, and the tragic history of Dora's life.
Includes bibliographical references and index
Keywords: Biografie; Diamant; Dora <1902-1952>; Kafka; Franz <1883-1924>; Diamant; Dora; Kafka; Franz; Liefdesleven